A new species and two new records of the genus Tycherobius Bolland (Acari: Camerobiidae) from Turkey. Issue 3 (2nd April 2016) - Ulucay, Ismail; Koc, Kamil; Akyol, Mustafa
ABSTRACT: A new species of the genus Tycherobius anatolicus sp. nov . collected from soil and litter under Crataegus sp. and Juglans sp. in Turkey is described and illustrated based on adult females. Additionally, T. iranensis Khanjani, Yazyanpanah, Ostovan and Asali Fayaz 2012 and T. sahragardi Khanjani, Hajizadeh, Hoseini and Jalili 2013 are recorded for the first time in Turkey. A comparison of characters of adult females of the genus Tycherobius is given and a key to known species of Tycherobius is provided.